(untitled) (Journal of Scientific Research, 2020)
Coronal mass ejection (CME) and Corotating interaction region (CIR), a dynamic phenomenon associated with the sun, is widely acknowledged as the main causative factor for the occurrence of the geomagnetic storms. In the present investigation, we studied the influence of solar wind parameters and interplanetary magnetic field (IMFBz) on two severe geomagnetic storms (Dst=<-200 nT) occurred during March and June 2015 using magnetic data recorded at four low latitude Indian magnetic observatories namely Jaipur (Rajasthan), Desalpar (Gujarat), Alibag (Maharastra) and Hyderabad (Telangana). Residual H-component of magnetic field distinctly distinguish the different phases of storms. Solar wind density and pressure are more influencive factors during main phase of the magnetic storm with observed high MS coherence (>0.8) with the H-comp. Dynamic spectrum of H-component of magnetic field at low latitudes and solar wind parameters reveals a burst-like nature during the main phase of these storms. During Ionospheric Disturbance Dynamo (Ddyn) for March Storm, it is observed that American sector has downward movement in H-component of magnetic field and prominent attenuation of EEJ in African and Indian sectors. Similarly, for June storm, downward H-component movement is observed in both the American and African sectors and attenuation of EEJ at Indian sector.